Harrison's principles of internal medicine - Fauci, Anthony S.; Loscalzo, Joseph (New York : McGraw Hill, 2022)
This book presents a sharp focus on the clinical presentation of disease, expert in-depth summaries of pathophysiology and treatment, and includes highlights of emerging frontiers of science and medicine--
Includes bibliographical references and index.
Keywords: Internal Medicine